Chronic care provision in general practices and association with patient level outcomes: a nationwide cohort study - Anders Prior; Claus Høstrup Vestergaard; Nynne Bech Utoft; Peter Vedsted; Susan M. Smith; Mogens Vestergaard; Morten Fenger-Grøn (BMC Medicine)
Abstract Background General practice provides long-term care for most people living with long-term conditions, but the impact of generic chronic care provision on patient outcomes has not been examined on a national level. We aimed to investigate whether the provision of chronic care services in general practice is associated with potentially inappropriate medications (PIMs) and potentially preventable hospitalisations in listed patients. Methods Nationwide cohort study using linked health registry data covering 4.42 million patients (18 + years) listed with general practices in Denmark in 2019 (n = 1769). The exposure was the patient’s practice listing. Practices were grouped evenly into low, medium, or high level of service provision (chronic care consultations, chronic care procedures, and daytime consultations) after adjustment for patient case-mix and multimorbidity. Sub-group analyses were based on list size, morbidity load, deprivation score, and urbanisation. The outcomes at patient level were number of patient days with PIMs (modified STOPP-START criteria) and number of potentially preventable hospitalisations. Results In practices providing high levels of chronic care consultations, the listed patients had a 1.2% lower risk of PIMs compared to the medium-level group (incidence rate ratio [IRR] 0.988, 95% confidence interval [CI] 0.977 to 0.999, corresponding to 3600 fewer patient years of PIMs per year) and an IRR of 0.964 (95% CI 0.927 to 1.002) for potentially preventable hospitalisations. In practices providing high levels of chronic care procedures, patients had a 1.7% lower risk of PIMs (IRR 0.983, 95% CI 0.972 to 0.993, 5500 fewer patient years of PIMs) and an 8.6% lower risk of potentially preventable hospitalisations (IRR 0.914, 95% CI 0.879 to 0.950, 3700 fewer potentially preventable hospitalisations per year). High levels of daytime consultations were associated with higher risk of PIMs, but not with potentially preventable hospitalisations. We found an inverse dose–response relationship between chronic care provision and adverse outcomes. The findings were stable between different practice characteristics and patient populations. Conclusions Patients experienced fewer potentially inappropriate medications and potentially preventable hospitalisations if listed at a general practice with high chronic care provision, regardless of other practice characteristics.